ANALISIS LAYANAN INFORMASI TENTANG PERKEMBANGAN SOSIAL REMAJA PADA SISWA KELAS VII SEKOLAH MENENGAH PERTAMA NEGERI 3 PONTIANAK - Lara, Resta; Yusuf, Abas; Lestari, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe Information service is a series of activities in order to provide assistance to students by providing information that can be used to make a further education plan. Therefore, the researcher wanted to know more about the information service by the guidance and counseling teacher on the development of adolescent social in class VII SMP Negeri 3 Pontianak. The problem of this research is